Perinatal and Maternal Outcomes of Pregnancies with Preterm Premature Rupture of Membranes - Alakbarlı, Khayala; Arıca, Görkem; Bayraktar, Elif; Alıcı-Davutoğlu, Ebru; Madazlı, Rıza (Cerrahpaşa Medical Journal, 2025)
Objective: To evaluate the maternal and perinatal outcomes of pregnancies with preterm premature rupture of membranes (PPROM) and to explore the perinatal and obstetric outcomes according to gestational age at the time of PPROM. Methods: This retrospective study included 316 singleton pregnancies with PPROM between 16+0 and 36+6 weeks of gestation. Perinatal and maternal outcomes according to gestational age at the time of PPROM are evaluated. Results: The mean latency duration was 7.5 ± 13.8 days and the incidence of latency ≥15 days was 14.6%. There was a significant negative correlation between the gestational week at diagnosis of PPROM and the duration of the latent period (r = −0.422, P < .001). Incidences of survival were 6.2%, 80.5%, 91.8%, and 100% in pregnancies with an onset of PPROM at 16+0 to 23+6, 24+0 to 27+6, 28+0 to 32+6, and 33+0 to 36+6 weeks’ gestation, respectively. Among the 249 liveborn infants, 4.4%, 3.1% and 1.3% had vision impairment, bronchopulmonary dysplasia, and cerebral palsy respectively at 2 years’ corrected age. Incidences of survival without long-term sequelae were 6.2%, 55.6%, 73.8%, and 100% in pregnancies with an onset of PPROM at 16+0 to 23+6, 24+0 to 27+6, 28+0 to 32+6, and 33+0 to 36+6 weeks’ gestation, respectively. There was a significant negative correlation between chorioamnionitis and gestational age at diagnosis of PPROM (r = −0.173, P = .002). Conclusion: Expectant management if not otherwise contraindicated is the choice of treatment in pregnancies after 24 weeks of gestation, and perinatal survival rates reaching 95% can be achieved with proper management. Cite this article as: Alakbarlı K, Arıca G, Bayraktar E, Alıcı-Davutoğlu E, Madazlı R. Perinatal and maternal outcomes of pregnancies with preterm premature rupture of membranes. Cerrahpaşa Med J. 2025; 49, 0114, doi: 10.5152/cjm.2025.23114.